ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS III PADA MATERI PENGUKURAN WAKTU SD NEGERI TLOGOSARI WETAN 02 SEMARANG - Karimah, Cikal Damayanti; Cahyadi, Fajar; Subekti, Ervina Eka (Jurnal Sinektik, 2021)
Analysis of Mathematics Learning Difficulties for Class III Students on Time Measurement Material at SD Negeri Tlogosari Wetan 02 Semarang. This study aims to describe learning difficulties and the factors that affect the learning difficulties of mathematics in the time measurement material. This type of research is descriptive qualitative. The research subjects were 40 grade III students of SD Negeri Wetan 02 Semarang. The instruments used were questions, interviews, documentation, questionnaires and observations. The results obtained in this study are: (a) Difficulties in learning mathematics in the material of time measurement include: difficulty in determining time units, calculating skills and difficulties in understanding the concept of time measurement. (b) Factors affecting the difficulty of learning mathematics in the time measurement material are internal factors including student attitudes, physical health, and motivation to learn mathematics. Meanwhile, external factors include teaching variations, use of media and infrastructure.